Predicting Treatment Outcomes from Prefrontal Cortex Activation for Self-Harming Patients with Borderline Personality Disorder: A Preliminary Study - Ruocco, Anthony C.; Rodrigo, Achala H.; McMain, Shelley F.; Page-Gould, Elizabeth; Ayaz, Hasan; Links, Paul S. (Frontiers in Human Neuroscience, 2016)
Self-harm is a potentially lethal symptom of borderline personality disorder (BPD) that often improves with dialectical behavior therapy (DBT). While DBT is effective for reducing self-harm in many patients with BPD, a small but significant number of patients either does not improve in treatment or ends treatment prematurely. Accordingly, it is crucial to identify factors that may prospectively predict which patients are most likely to benefit from and remain in treatment. In the present preliminary study, twenty-nine actively self-harming patients with BPD completed brain-imaging procedures probing activation of the prefrontal cortex during impulse control prior to beginning DBT and after seven months of treatment. Patients that reduced their frequency of self-harm the most over treatment displayed lower levels of neural activation in the bilateral dorsolateral prefrontal cortex prior to beginning treatment, and they showed the greatest increases in activity within this region after seven months of treatment. Prior to starting DBT, treatment non-completers demonstrated greater activation than treatment-completers in the medial prefrontal cortex and right inferior frontal gyrus. Reductions in self-harm over the treatment period were associated with increases in activity in right dorsolateral prefrontal cortex even after accounting for improvements in depression, mania, and BPD symptom severity. These findings suggest that pre-treatment patterns of activation in the prefrontal cortex underlying impulse control may be prospectively associated with improvements in self-harm and treatment attrition for patients with BPD treated with DBT.